Infection by Nanophyetus salmincola and Toxic Contaminant Exposure in Out‐migrating Steelhead from Puget Sound, Washington: Implications for Early Marine Survival. Issue 2 (30th April 2018) - Chen, M. F.; O'Neill, S. M.; Carey, A. J.; Conrad, R. H.; Stewart, B. A.; Snekvik, K. R.; Ylitalo, G. M.; Hershberger, P. K.
Abstract: Out‐migrating steelhead Oncorhynchus mykiss from four Puget Sound rivers and associated marine basins of Puget Sound in Washington State were examined for the parasite, Nanophyetus salmincola in 2014 to determine whether recent trends in reduced marine survival are associated with the presence of this pathogen. A subset of steelhead from three of these river–marine basin combinations was analyzed for the presence of persistent organic pollutants (POPs) to assess whether exposure to these contaminants is a contributing factor to their reduced marine survival. The prevalence and parasite load of N. salmincola were significantly higher in fish from central and southern Puget Sound than in fish from river systems in northern Puget Sound. The proportion of steelhead samples with concentrations of POPs higher than adverse effects thresholds (AETs) or concentrations known to cause adverse effects was also greater in fish from the central and southern regions of Puget Sound than in those from the northern region. Polybrominated diphenyl ether concentrations associated with increased disease susceptibility were observed in 10% and 40% of the steelhead sampled from central and southern Puget Sound regions, respectively, but in none of the fish sampled from the northern region. The AET for polychlorinated biphenyls was exceeded in steelhead collected from marine habitats: 25% of the samples from the marine basins in the central and southern regions of Puget Sound and 17% of samples from northern Puget Sound region. Both N. salmincola and POP levels suggest there are adverse health effects on out‐migrating steelhead from one southern and one central Puget Sound river that have lower early marine survival than those from a river system in northern Puget Sound.